A MODEL OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR IMPROVEMENT BASED ON INSTRINSIC MOTIVATION AND ORGANIZATIONAL JUSTICE IN REGIONAL SECRETARIAT OF SEMARANG REGENCYA MODEL OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR IMPROVEMENT BASED ON INSTRINSIC MOTIVATION AND ORGANIZATIONAL JUSTICE IN REGIONAL SECRETARIAT OF SEMARANG REGENCY - Ika Rusmawati; Mutamimah Mutamimah (UNISSULA, 2017)
Good Organizational Citizenship Behavior (OCB) needs to be supported by a strong commitment from human resources since the stronger the employees’ commitment, the higher the OCB will be. The improvemnet of Human Resource commitment needs to be supported by strong intrinsic motivation from human resources and organizational justice which is able to encourage human resources in improving organizational citizenship behavior (OCB). This study was conducted in Regional Secretariat of Semarang regency to 118 civil servants working there. Census was used as the sampling technique in this study in which every member of the population had the same opportunity to be taken as the research sample. Regressive analysis of path analysis model (path analysis) was used as the analysis technique. The research revealed that intrinsic motivation and organizational justice had a significant positive effect on organizational commitment and OCB, while commitment had a significant positive effect on OCB.Keywords : intrinsic motivation, organizational justice, commitment and OCB.